Term in the linguistic information science (Journal of Information Technologies in Education (ITE), 2009)
This article is devoted to description of the lexicographical and encyclopaedic computer database of Ukrainian linguistic terms. This database comprises of 4 lists: one alphabetized list, a list with translations, a list with descriptions and thesaurus containing generally over 3400 terms in the fields of morphology, syntax, semantics, lexicon, and computer linguistics. There are also desribed technologies and techniques of construction of the information and retrieval system which may function as a single reference and encyclopaedic system or as an integral part of any other intellectual system.
Keywords: informationand retriaval system; linguistic modelling; term; thesaurus; thesaurus relations